The effects of hyperglycaemia on changes during reperfusion following focal cerebral ischaemia in the cat. Issue 7 (July 1985) - Venables, G S; Miller, S A; Gibson, G; Hardy, J A; Strong, A J
Abstract : The effects of isosmolar loads of glucose and saline after onset of focal cerebral ischaemia (middle cerebral artery occlusion) were compared in cats. In cats given saline cerebral blood flow (CBF) fell and then rose slightly on the marginal gyrus (infarct penumbra). There was a sustained fall in CBF on the suprasylvian and ectosylvian gyri (infarct core). Reperfusion restored blood flow to preocclusion levels with no overall postischaemic hypoperfusion. Below ischaemic flows of 14 ml/100 g/min brain specific gravity was reduced in a smaller proportion of gyri by contrast with non reperfused cortex, suggesting that in some gyri resolution of cerebral oedema had taken place. GABA uptake was normal in the infarct core, but was reduced within the ischaemic penumbra. In animals given glucose after occlusion, CBF fell on the marginal gyrus during reperfusion. The degree of resolution of cerebral oedema was less than in saline infused cats. GABA uptake showed a pattern of abnormality similar to that seen in saline infused cats, except that uptake values were lower in the infarct core. Pial surface potassium activity remained elevated in the penumbra following reperfusion in glucose infused cats, but returned to normal in saline infused cats. Implications for the management of cerebral ischaemia in man are discussed.